Diving Deep: Illuminating Coastal Minds on Marine Ecologies through Learning Video - Alfian Carli; Defitri Aldanika; Kurniawan Anang; Akbar Gilang (SHS Web of Conferences)
In this research, students at SMPN 9 Tanjungpinang, a school in a unique coastal region of Indonesia which is Tanjungpinang, are asked about their knowledge of and concerns about the maritime environment. 33 coastal students filled out written questionnaires as part of a descriptive qualitative research approach, and National Geographic educational videos were also used to collect data. The researchers used narrative inquiry design to analyze the data. The results show that students have serious concerns about how human activity is giving bad impact to marine ecosystem. Combining the findings of the research, it is obvious that human activity poses a major threat to coastal ecosystems, which are crucial to the development and survival of marine species. The joint assault of indiscriminate trash dumping and trawling techniques manifests itself as a powerful force undermining the fundamental elements of these ecosystems.